Heavy Metal Pollution Assessment in surface and groundwater in the Ponce Enríquez mining area, Ecuador. (LACCEI, 2024)
Mining activities have been carried out in Ponce Enríquez for more than 40 years. However, illegal, and anti-technical mining practices have caused pollution and environmental degradation of the water resources. This study aims to assess the pollution degree of surface and groundwater in the Río Tenguel and Río Siete watersheds. Eighteen water samples from rivers and wells were taken, and the concentration of Pb, Fe, Zn, Mn, Cr, Cu, As, and Cd was analyzed. The level of water contamination was evaluated by applying the Metal Index (MI). As a result, an enrichment in the concentration of Cu, Pb, and As was evidenced, which exceeded the maximum permissible limit of the Ecuadorian regulations, up to 128, 12, and 10 times, respectively. Regarding the MI, 60% of the surface water samples were seriously affected, where the Siete river is the most polluted. These results reveal an overview of the pollution degree in Ponce Enriquez water resources, and this information can serve as an input for decision makers on water protection issues.